Pendekatan Maqashid Syariah Terhadap Konsep Makanan Halalan Thoyyiban Dalam Islam - Siti Maheran; Asrizal Saiin; Muhammad April; Muh Rizki (TERAJU: Jurnal Syariah dan Hukum, 2022)
The command to consume food that is lawful and good has been clearly and clearly conveyed by Allah swt in the Qur'an, and it can be understood in the concept of maqashid ash-syariah. This study aims to understand how the maqashid sharia concept can provide an approach in understanding the intent and purpose of halalan thoyyiban food in Islam. The method used in this research is descriptive qualitative research method with Jenie. The results of this study are that food halalan thoyyiban in Islam is the embodiment of the main elements of the objectives of the Shari'a (maqashid ash-syariah), namely maintaining religion (hifdz ad-Diin), guarding the soul (hifdz an-Nafs), guarding reason (hifdz al-'Aql), guarding offspring (hifdz an-Nasl), and guarding property (hifdz al-Mal).